Music as a window into real-world communication - Izen, Sarah C.; Cassano-Coleman, Riesa Y.; Piazza, Elise A. (Frontiers in Psychology, 2023)
Communication has been studied extensively in the context of speech and language. While speech is tremendously effective at transferring ideas between people, music is another communicative mode that has a unique social power, bringing people together through joint music-making and listening and facilitating the deep expression of emotions in a variety of everyday contexts. Research has begun to examine the behavioral and neural correlates of the joint action required for successful musical interactions, but it has yet to fully account for the rich, dynamic nature of musical communication. We review the current literature in this area and propose that naturalistic musical paradigms are an ideal way to study communication.